Restorations retreatment prevalence in composite resin and silver amalgam - Julia Sarmento Persici; Mariana Dias Flor Ribeiro; Flávia Bittencourt Pazinatto (Associação Brasileira de Odontologia, 2018)
Objective: the objective of this study was to identify the frequency and causes of retreatment (replacement/ repair), restorations longevity, classes and dental elements most affected. Material and Methods: the methodology was based in the analysis of records of clinical disciplines of the Federal University of Espírito Santo (UFES) between 2013 and 2015. Results: about 24,5% of composite resin restorations and 29% of amalgam restorations were remade. The replacement was more prevalent (71,38%) in comparison to the repair (7,39%); 21,22% of the retreatments were not specified. The highest prevalence of failure occurred due to caries. 3,37% of the restorations performed in the disciplines failed and were remade. The longevity ranged from three days to about two years, with a higher prevalence of failures in up to six months after the restoration was completed. The teeth and dental classes most represented were, respectively, incisors and classes III, for composite resin; and for amalgam, lower molars and classes I. Conclusion: the longevity was achieved within six months after restoration and replacement was the most prevalent retreatment. Secondary caries were the predominant fault and the group of teeth and dental classes most prevalent in the treatment of amalgam and composite resin restorations were, respectively, the lower and class I molars and the incisors and classes III.